Using wood for fuel in the North-Eastern Part of India - A review of the current situation - Ruby,; Tiwari, Garima (International Journal of Environment, Agriculture and Biotechnology, 2024)
The domestic usage of fuelwood as the primary energy source has created considerable deforestation in North East India. The extraction of most fuel wood from wood is one of the principal causes of disturbance to the native forest flora of north east India. In this study, scientific journals, edited books, and other scientific databases were studied to examine fuelwood consumption trends in the North East India. A total of 162 plant species from 53 families were utilized as fuel by the natives of the region of seven sister states, along with Sikkim, according to a review of the relevant literature. Depending on their local availability, different plant species have been used as fuels in diverse locations. Schima wallichi, A. procera, and Toona ciliata were the most profound species reported in scientific literature. The FVI ranges from 22678 to 2.43 in the listed species. The accumulated data on fuelwood consumption patterns and fuelwood species utilized in the NEH could serve as a baseline for future studies and policy formulation, thus aiding in conserving the region's forest resources.